Detecting Muscle Invasion of Bladder Cancer Using a Proposed Magnetic Resonance Imaging Strategy. Issue 4 (17th May 2021) - Wang, Xiangyu; Tu, Ning; Sun, Feng; Wen, Zhi; Lan, Xinxin; Lei, Yi; Cui, Enming; Lin, Fan
Abstract : Background: Accurate evaluation of the invasion depth of tumors with a Vesical Imaging‐Reporting and Data System (VI‐RADS) score of 3 is difficult. Purpose: To evaluate the diagnostic performance of a new magnetic resonance imaging (MRI) strategy based on the integration of the VI‐RADS and tumor contact length (TCL) for the diagnosis of muscle‐invasive bladder cancer (MIBC). Study type: Single center, retrospective. Subjects: A group of 179 patients with a mean age of 67 years (range, 24.0–96.0) underwent multiparametric MRI (mpMRI) before surgery, including 147 (82.1%) males and 32 (17.9%) females. Twenty‐four (13.4%), 90 (50.3%), 43 (24.0%), 15 (8.4%), and 7 (3.9%) cases were Ta, T1, T2, T3, and T4, respectively. Field Strength/Sequence: A 1.5 T and 3.0 T, T2‐weighted turbo spin‐echo (TSE), single‐shot echo‐planar (SS‐EPI), diffusion‐weighted imaging (DWI), and T1‐weighted volumetric interpolated breath‐hold examination (T1‐VIBE). Assessment: Three radiologists independently graded the VI‐RADS score and measured the TCL on index lesion images. A proposed MRI strategy called VI‐RADS_TCL was introduced by modifying the VI‐RADS score, which was downgraded to VI‐RADS 3F (equal to a VI‐RADS score of 2) if VI‐RADS = 3 and TCL < 3 cm. Statistical Tests: Intraclass correlation coefficients (ICCs), Mann–Whitney U test, chi‐square tests, receiver operating characteristic (ROC) curves, and 2 × 2 contingency tables were applied. Results: Inter‐reader agreement values were 0.941 (95% CI, 0.924–0.955) and 0.934 (95% CI, 0.916–0.948) for the TCL and VI‐RADS score. The TCL was significantly increased in the MIBC group (6.40–6.85 cm) compared with the NMIBC group (1.98–2.45 cm) ( P  < 0.05). The specificity and positive predictive values (PPV) of VI‐RADS_TCL were 82.46%–87.72% and 90.91%–91.59%, which were significantly greater than VI‐RADS score ( P  < 0.05). Additionally, 52.17%–55.88% NMIBC lesions with VI‐RADS 3 were downgraded to 3F by using VI‐RADS_TCL. Data Conclusion: The proposed MRI strategy could reduce the false‐positive rate of lesions with a VI‐RADS score of 3 while retaining sensitivity. Evidence Level: 4 Technical Efficacy: 2